Program aktywizacji obszarów wiejskich - próba oceny jego efektywności - Węgrzyn, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The main goal of this paper is both to identify the problem of the unemployment in the rural area and to attempt estimation of efficiency of the Rural Development Programme in range of extra-agricultural creation of work-place through conceding of microcredits. Rural Development Programme, which was realized in Poland in the 2001-2004 period, had the task of contributing for widely understood economic development of village. Effects of component A - Microcredits, are first of all created work-places (2941).(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 172-182